Inorganic coating and its preparation method and application
By using inorganic coatings prepared by inorganic materials such as ZnO-SiO2 and ZnO-TiO2 sol, the shortcomings of existing photovoltaic self-cleaning coatings in terms of permeability, dust resistance and self-cleaning properties are solved, and the combination of high light transmittance and excellent self-cleaning performance is achieved, which is suitable for large-scale promotion and application.
Patent Information
- Application Number
- CN202411794367.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The existing photovoltaic self-cleaning coatings have shortcomings in terms of permeability, dust resistance and self-cleaning properties, and the preparation method is complex and the equipment cost is high, which limits large-scale promotion and application.
The inorganic permeability enhancer ZnO-SiO2 sol and the photocatalyst ZnO-TiO2 sol are used to combine inorganic film forming agents and solvents to prepare inorganic coatings through simple process operations, significantly improving light transmittance and self-cleaning ability and reducing preparation costs.
It significantly improves the light transmittance and self-cleaning ability of the paint, enhances stability and weather resistance, is suitable for long-term outdoor use, and reduces preparation and maintenance costs.
Smart Images

Figure CN119264709B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coatings, and in particular to an inorganic coating and a preparation method and application thereof. Background Art
[0002] With the continuous advancement of photovoltaic technology and building materials, the market demand for improved optical performance and self-cleaning ability is growing. Although the existing photovoltaic self-cleaning coating has a certain cleaning effect, it still has shortcomings in terms of transparency, dust resistance and self-cleaning.
[0003] In the Chinese invention patent application with publication number CN101168475A, a super-hydrophilic coating is prepared by electrostatic assembly, but it does not have the ability to decompose organic pollutants. After long-term use, its durability is insufficient and it is easily blocked by pollutants, which affects the self-cleaning effect.
[0004] The Chinese invention patent application with publication number CN107892826A proposes a composite self-cleaning nano coating that combines conductive particles, photocatalysts and super-hydrophilic functions to achieve instant self-cleaning. The coating has anti-static, super-hydrophilic and photolysis functions, but the light transmittance of the coating is low and cannot meet the light transmittance requirements in photovoltaic applications, which is crucial to the photoelectric conversion efficiency of photovoltaic cells.
[0005] The Chinese invention patent application with publication number CN107217232A proposes an acid-base corrosion-resistant ZnO film and a preparation method thereof. The film is prepared by magnetron sputtering technology, but this preparation method has many inconveniences in production efficiency and practical application, such as high equipment cost and complex process, which limits its large-scale promotion and application.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] One of the purposes of the present invention is to provide an inorganic coating to at least solve one of the technical problems existing in the prior art. The inorganic coating provided by the present invention can significantly improve the optical transmittance and has excellent dustproof and self-cleaning properties.
[0008] The second object of the present invention is to provide a method for preparing an inorganic coating, which has simple process operation, does not require the use of equipment with high maintenance costs such as a magnetron sputtering device, and can achieve large-scale batch production.
[0009] The third object of the present invention is to provide an inorganic coating or an inorganic coating prepared by a method for preparing an inorganic coating for use in surface treatment of inorganic materials.
[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0011] In a first aspect, the present invention provides an inorganic coating, the inorganic coating comprising the following components: an inorganic transmittance enhancer, a photocatalyst, an inorganic film-forming agent and a solvent;
[0012] Wherein, the inorganic permeability enhancer includes ZnO-SiO 2 Sol, the photocatalyst comprises ZnO-TiO 2 Sol.
[0013] Furthermore, the inorganic coating comprises the following components by mass percentage:
[0014] 0.1-2% inorganic transmittance enhancer, 0.1-2% photocatalyst, 0.1%-5% inorganic film-forming agent and the balance solvent;
[0015] Preferably, the inorganic coating comprises the following components by mass percentage: 0.1-1% inorganic transmittance enhancer, 0.1-1% photocatalyst, 0.1%-2% inorganic film-forming agent and the balance solvent.
[0016] Further, the inorganic permeability enhancer is prepared by hydrolyzing zinc salt and silicate;
[0017] Preferably, the ratio of the amount of zinc salt to the amount of silicate material is 1:20-3:1, preferably 1:1-1:5;
[0018] Preferably, the zinc salt comprises at least one of zinc acetate and zinc chloride;
[0019] Preferably, the silicate includes at least one of tetramethyl silicate and tetraethyl silicate.
[0020] Further, the photocatalyst is prepared by hydrolyzing zinc salt and titanate;
[0021] Preferably, the ratio of the amount of zinc salt to the amount of titanate substance is 1:10-3:1, preferably 1:1-1:5;
[0022] Preferably, the zinc salt comprises at least one of zinc acetate and zinc chloride;
[0023] Preferably, the titanate includes at least one of ethyl titanate, isopropyl titanate and butyl titanate.
[0024] Further, the inorganic film-forming agent includes silica sol;
[0025] Preferably, the silica sol includes at least one of acidic silica sol, alkaline silica sol and neutral silica sol;
[0026] Preferably, the silica sol has a particle size of 2 nm-200 μm, preferably a particle size of 2 nm-100 nm.
[0027] Furthermore, the solvent includes at least one of ethanol and isopropanol, and water.
[0028] In a second aspect, the present invention provides a method for preparing the inorganic coating, comprising the following steps:
[0029] The inorganic transmittance enhancer, the photocatalyst and the inorganic film-forming agent are mixed to obtain the inorganic coating.
[0030] Further, the zinc salt and the silicate are mixed and reacted to obtain an inorganic permeability enhancer;
[0031] Preferably, the process of mixing the zinc salt and the silicate further comprises: adding a solvent containing an alcohol amine, stirring at room temperature, and reacting;
[0032] Preferably, the alcoholamine includes at least one of ethanolamine, diethanolamine and triethanolamine;
[0033] Preferably, the stirring time is 8-12 h.
[0034] Further, zinc salt and titanate are mixed and reacted to obtain a photocatalyst;
[0035] Preferably, the process of mixing the zinc salt and the titanate further comprises: adding to a solvent containing an acid, stirring at room temperature, performing a primary reaction, and then adding to adjust the pH to 7-9, stirring at room temperature, and performing a secondary reaction;
[0036] Preferably, the acid agent comprises at least one of hydrochloric acid, acetic acid, phosphoric acid and sulfuric acid;
[0037] Preferably, the pH is adjusted by adding an alcohol amine;
[0038] Preferably, the stirring time of the primary reaction is 7-9 h;
[0039] Preferably, the stirring time of the secondary reaction is 1-2 h.
[0040] In a third aspect, the present invention provides an application of the inorganic coating or the inorganic coating prepared by the method for preparing the inorganic coating in the surface treatment of inorganic materials.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] The inorganic coating provided by the present invention comprises an inorganic permeability enhancer of ZnO-SiO 2 Sol, using zinc oxide / silicon oxide sol to achieve inorganic anti-reflection, significantly improving the light transmittance of the coating, while also enhancing the stability and weather resistance of the coating, making it suitable for long-term use in outdoor environments; the photocatalyst uses ZnO-TiO 2Sol, zinc oxide can enhance the photocatalytic ability of titanium dioxide, improve the efficiency of photocatalytic reaction, thereby enhancing the degradation ability of organic dirt and improving the self-cleaning ability. At the same time, titanium dioxide and zinc oxide are semiconductors with conductivity, which can reduce the surface resistance of the coating and improve the dustproof ability. Titanium dioxide can protect zinc oxide and enhance the outdoor stability of zinc oxide; inorganic film-forming agents and inorganic permeability enhancers can cooperate with each other to form good hydrophilicity and have good rainwater self-cleaning properties under lightless conditions. The inorganic coating provided by the present invention can improve optical transmittance and has excellent dustproof and self-cleaning properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0044] Figure 1 This is a dust-proof effect diagram of the photovoltaic panel slope after the inorganic coating prepared in Example 13 is applied;
[0045] Figure 2 This is a picture of the dust prevention effect of existing photovoltaic panels that have not been treated. DETAILED DESCRIPTION
[0046] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.
[0047] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] The first aspect of the present invention provides an inorganic coating, which comprises the following components: an inorganic transmittance enhancer, a photocatalyst, an inorganic film-forming agent and a solvent;
[0049] Wherein, the inorganic permeability enhancer includes ZnO-SiO 2 Sol, the photocatalyst comprises ZnO-TiO 2 Sol.
[0050] In the present invention, among the components of the inorganic coating, the inorganic permeability enhancer is ZnO-SiO 2 Sol, using zinc oxide / silicon oxide sol to achieve inorganic anti-reflection, significantly improving the light transmittance of the coating, while also enhancing the stability and weather resistance of the coating, making it suitable for long-term use in outdoor environments; the photocatalyst uses ZnO-TiO 2 Sol, zinc oxide can enhance the photocatalytic ability of titanium dioxide, improve the efficiency of photocatalytic reaction, thereby enhancing the degradation ability of organic dirt and improving the self-cleaning ability. At the same time, titanium dioxide and zinc oxide are semiconductors with conductivity, which can reduce the surface resistance of the coating and improve the dustproof ability. Titanium dioxide can protect zinc oxide and enhance the outdoor stability of zinc oxide; inorganic film-forming agent and inorganic permeability enhancer can cooperate with each other to form good hydrophilicity and have good rainwater self-cleaning property. The inorganic coating provided by the present invention is an inorganic permeability enhancer super hydrophilic self-cleaning dustproof coating, which can improve optical transmittance and has excellent dustproof and self-cleaning performance. It can reduce the frequency of cleaning and maintenance of photovoltaic panels, and reduce maintenance costs while increasing overall power generation efficiency.
[0051] Specifically: (1) Regarding transmittance enhancement: The inorganic coating provided by the present invention has good transmittance enhancement. The coating made of the inorganic coating provided by the present invention can achieve an transmittance enhancement effect of more than 4% on photovoltaic glass and ordinary glass, while the transmittance enhancement effect of coatings prepared by silicon titanium sol can only reach about 2% at present; the present invention combines zinc oxide with silicon oxide sol-gel method to achieve inorganic transmittance enhancement, significantly improving the transmittance of the coating. The average transmittance of the coating in the most critical wavelength range of 400-800 nm in photovoltaics can reach more than 4%, showing good wide-spectrum transmittance enhancement. At the same time, the composite material of zinc oxide and silicon oxide sol can improve the stability and weather resistance of zinc oxide used alone, so that the coating can be used outdoors for a long time.
[0052] (2) Regarding photocatalytic ability: The inorganic coating provided by the present invention has strong photocatalytic ability. 2 Heterojunction method is used to achieve efficient photocatalytic performance, ZnO-TiO 2 The heterojunction can effectively separate photogenerated electrons and holes, improve the efficiency of photocatalytic reaction, and thus enhance the degradation ability of organic dirt; under ultraviolet light, ZnO can excite TiO 2 Produce more free radicals to accelerate the dirt decomposition process; TiO 2 The surface can be kept super-hydrophilic by light exposure, and ZnO can further enhance this property, making dirt easier to be washed away by rainwater, thereby improving the self-cleaning ability; ZnO-TiO 2 The heterojunction will also improve the light transmittance to a certain extent and achieve a certain anti-reflection effect.
[0053] (3) Anti-static and dustproof capability: The inorganic coating provided by the present invention has strong dustproof capability. The present invention uses titanium oxide / zinc oxide semiconductors to reduce the surface resistance of the coating to 10 8 Ω order of magnitude, compared to the coating currently on the market 10 10 Ω order of magnitude, with better dust resistance.
[0054] (4) Regarding hydrophilicity: The present invention adopts an inorganic film-forming agent, which has good hydrophilicity both in the presence of light and in the absence of light, and has good self-cleaning properties in rainwater.
[0055] In some preferred embodiments, the inorganic coating comprises the following components by mass percentage:
[0056] 0.1-2% inorganic transmittance enhancer, 0.1-2% photocatalyst, 0.1%-5% inorganic film-forming agent and the balance solvent;
[0057] Taking the total mass of the inorganic coating as 100%, the addition amount of the inorganic transmittance enhancer is 0.1-2%, for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, etc.;
[0058] Taking the total mass of the inorganic coating as 100%, the amount of the photocatalyst added is 0.1-2%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, etc.;
[0059] Based on the total mass of the inorganic coating as 100%, the addition amount of the inorganic film-forming agent is 0.1%-5%, for example, it can be 0.1%, 0.5%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc.;
[0060] Preferably, the inorganic coating comprises the following components by mass percentage: 0.1-1% inorganic transmittance enhancer, 0.1-1% photocatalyst, 0.1%-2% inorganic film-forming agent and the balance solvent.
[0061] Taking the total mass of the inorganic coating as 100%, the addition amount of the inorganic transmittance enhancer is 0.1-1%, for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc.;
[0062] Based on the total mass of the inorganic coating as 100%, the amount of the photocatalyst added is 0.1-1%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc.;
[0063] Taking the total mass of the inorganic coating as 100%, the added amount of the inorganic film-forming agent is 0.1%-2%, for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, etc.
[0064] In some preferred embodiments, the inorganic permeability enhancer is prepared by hydrolyzing a zinc salt and a silicate;
[0065] Preferably, the ratio of the amount of zinc salt to the amount of silicate material is 1:20-3:1, for example, it can be 1:20, 1:10, 1:2, 1:1, 2:1, 3:1, etc., and more preferably 1:1-1:5, for example, it can be 1:1, 1:2, 1:3, 1:4, 1:5, etc.;
[0066] Preferably, the zinc salt comprises at least one of zinc acetate and zinc chloride;
[0067] In the present invention, the zinc salt is more preferably zinc acetate.
[0068] Preferably, the silicate includes at least one of tetramethyl silicate and tetraethyl silicate.
[0069] In the present invention, the silicate is further tetraethyl silicate.
[0070] In some preferred embodiments, the photocatalyst is prepared by hydrolyzing a zinc salt and a titanate;
[0071] Preferably, the ratio of the amount of zinc salt to the amount of titanate substance is 1:10-3:1, for example, it can be 1:10, 1:2, 1:1, 2:1, 3:1, etc., preferably 1:1-1:5, for example, it can be 1:1, 1:2, 1:3, 1:4, 1:5, etc.;
[0072] Preferably, the zinc salt comprises at least one of zinc acetate and zinc chloride;
[0073] Preferably, the titanate includes at least one of ethyl titanate, isopropyl titanate and butyl titanate.
[0074] In some preferred embodiments, the inorganic film-forming agent includes silica sol;
[0075] Preferably, the silica sol includes at least one of acidic silica sol, alkaline silica sol and neutral silica sol;
[0076] Preferably, the particle size of the silica sol is 2 nm-200 μm, for example, it can be 2 nm, 50 nm, 100 nm, 500nm, 1 μm, 10 μm, 50 μm, 100 μm, 150 μm, 200 μm, etc., and further preferably, it is 2 nm-100 nm, for example, it can be 2 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc.
[0077] In the present invention, silica sol is used as an inorganic film-forming agent, and suitable silica sol and the hydrolysis product of the mesosilicate in the inorganic permeability enhancer are selected to form good hydrophilicity, and good rainwater self-cleaning property can be achieved under lightless conditions.
[0078] In some preferred embodiments, the solvent includes at least one of ethanol and isopropanol, and water.
[0079] In the present invention, the solvent is further preferably a mixed solution of ethanol and water, and its concentration is 2%-98%, that is, it can be close to pure water or close to pure ethanol.
[0080] A second aspect of the present invention provides a method for preparing an inorganic coating, comprising the following steps:
[0081] The inorganic transmittance enhancer, the photocatalyst and the inorganic film-forming agent are mixed to obtain the inorganic coating.
[0082] In the present invention, the adopted process operation is simple and convenient, and there is no need to use equipment with high maintenance cost such as magnetron sputtering equipment, so large-scale batch production can be achieved.
[0083] In some preferred embodiments, a zinc salt and a silicate are mixed and reacted to obtain an inorganic permeability enhancer;
[0084] Preferably, the process of mixing the zinc salt and the silicate further comprises: adding a solvent containing an alcohol amine, stirring at room temperature, and reacting;
[0085] Preferably, the alcoholamine includes at least one of ethanolamine, diethanolamine and triethanolamine;
[0086] In the present invention, zinc salt and silicate are mixed, added into a solvent containing alcohol amine, and stirred at room temperature to achieve hydrolysis and condensation reaction, thereby obtaining a stable ZnO-SiO 2 Sol and alcohol amine can promote hydrolysis and condensation reactions, and increase the reaction rate and yield.
[0087] Preferably, the stirring time is 8-12 h, for example, it can be 8 h, 9 h, 10 h, 11 h, 12 h, etc.
[0088] In some preferred embodiments, zinc salt and titanate are mixed and reacted to obtain a photocatalyst;
[0089] Preferably, the process of mixing the zinc salt and the titanate further comprises: adding to a solvent containing an acid agent, stirring at room temperature, performing a primary reaction, then adjusting the pH to 7-9, for example, 7, 7.5, 8, 8.5, 9, etc., stirring at room temperature, and performing a secondary reaction;
[0090] Preferably, the acid agent comprises at least one of hydrochloric acid, acetic acid, phosphoric acid and sulfuric acid;
[0091] Preferably, the pH is adjusted by adding an alcohol amine;
[0092] In the present invention, zinc acetate and titanate are mixed and added to a solvent containing an acid agent, the acid agent is used to adjust the pH to 2-4, and then stirred at room temperature to achieve hydrolysis, and then the pH is adjusted to 7-9 with an alcohol amine, and stirring is continued until the condensation reaction is completed to obtain a stable ZnO-TiO 2 Sol.
[0093] Preferably, the stirring time of the primary reaction is 7-9 h, for example, 7 h, 7.5 h, 8 h, 8.5 h, 9 h, etc.;
[0094] Preferably, the stirring time of the secondary reaction is 1-2 h, for example, 1 h, 1.5 h, 2 h, etc.
[0095] A third aspect of the present invention provides an inorganic coating or an inorganic coating prepared by a method for preparing an inorganic coating and its use in surface treatment of inorganic materials.
[0096] In some preferred embodiments, the inorganic material includes at least one of a cement substrate, a glass substrate and a metal plate.
[0097] The application of the inorganic coating in the surface treatment construction of inorganic materials is mainly: using common methods such as spraying, rolling, brushing, etc. for construction. It can be constructed on the inclined surface of the installed photovoltaic panel, or on the horizontal surface or vertical surface, to form a self-cleaning coating with anti-reflection, dustproofing, etc. on the surface of the photovoltaic panel.
[0098] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0099] Example 1
[0100] This embodiment provides an inorganic coating, which includes the following components by mass percentage:
[0101] 0.1% inorganic transmittance enhancer, 2% photocatalyst, 0.1% inorganic film-forming agent and the balance solvent;
[0102] Among them, the inorganic permeability enhancer is ZnO-SiO 2 Sol, ZnO-SiO 2 The sol was prepared by hydrolyzing zinc acetate and tetraethyl silicate in a molar ratio of 1:20;
[0103] The photocatalyst is ZnO-TiO 2 Sol, ZnO-TiO 2 The sol was prepared by hydrolyzing zinc acetate and butyl titanate in a molar ratio of 3:1;
[0104] The inorganic film-forming agent silica sol is acidic silica sol with a particle size of 2 nm.
[0105] Example 2
[0106] This embodiment provides an inorganic coating, which includes the following components by mass percentage:
[0107] 2% inorganic transmittance enhancer, 0.1% photocatalyst, 5% inorganic film-forming agent and the balance solvent;
[0108] Among them, the inorganic permeability enhancer is ZnO-SiO 2 Sol, ZnO-SiO 2 The sol was prepared by hydrolyzing zinc acetate and tetraethyl silicate in a molar ratio of 3:1;
[0109] The photocatalyst is ZnO-TiO 2 Sol, ZnO-TiO 2 The sol was prepared by hydrolyzing zinc acetate and butyl titanate in a molar ratio of 1:10;
[0110] The inorganic film-forming agent silica sol is alkaline silica sol with a particle size of 200 μm.
[0111] Example 3
[0112] This embodiment provides an inorganic coating, which includes the following components by mass percentage:
[0113] 0.1% inorganic transmittance enhancer, 1% photocatalyst, 0.1% inorganic film-forming agent and the balance solvent;
[0114] Among them, the inorganic permeability enhancer is ZnO-SiO 2 Sol, ZnO-SiO 2The sol was prepared by hydrolyzing zinc acetate and tetraethyl silicate in a molar ratio of 1:1;
[0115] The photocatalyst is ZnO-TiO 2 Sol, ZnO-TiO 2 The sol was prepared by hydrolyzing zinc acetate and butyl titanate in a molar ratio of 1:5;
[0116] The inorganic film-forming agent silica sol is neutral silica sol with a particle size of 100 nm.
[0117] Example 4
[0118] This embodiment provides an inorganic coating, which includes the following components by mass percentage:
[0119] 1% inorganic transmittance enhancer, 0.1% photocatalyst, 2% inorganic film-forming agent and the balance solvent;
[0120] Among them, the inorganic permeability enhancer is ZnO-SiO 2 Sol, ZnO-SiO 2 The sol was prepared by hydrolyzing zinc acetate and tetraethyl silicate in a molar ratio of 2:4;
[0121] The photocatalyst is ZnO-TiO 2 Sol, ZnO-TiO 2 The sol was prepared by hydrolyzing zinc acetate and butyl titanate in a molar ratio of 1:1;
[0122] The inorganic film-forming agent silica sol is neutral silica sol with a particle size of 200 nm.
[0123] Example 5
[0124] This embodiment provides an inorganic coating, which includes the following components by mass percentage:
[0125] 0.2% inorganic transmittance enhancer, 0.2% photocatalyst, 0.6% inorganic film-forming agent and the balance solvent;
[0126] Among them, the inorganic permeability enhancer is ZnO-SiO 2 Sol, ZnO-SiO 2 The sol was prepared by hydrolyzing zinc acetate and tetraethyl silicate in a molar ratio of 1:5;
[0127] The photocatalyst is ZnO-TiO 2 Sol, ZnO-TiO 2 The sol was prepared by hydrolyzing zinc acetate and butyl titanate in a molar ratio of 2:4;
[0128] The inorganic film-forming agent silica sol is neutral silica sol with a particle size of 50 nm.
[0129] Example 6
[0130] This embodiment provides an inorganic coating, which is different from Embodiment 5 in that:
[0131] The zinc salt used in preparing the inorganic permeability enhancer is zinc chloride, and the silicate is tetramethyl silicate;
[0132] The zinc salt used in preparing the photocatalyst is zinc chloride, and the titanate is ethyl titanate;
[0133] The rest is consistent with Example 5.
[0134] Example 7
[0135] This embodiment provides an inorganic coating, which is different from the embodiment 5 in that it comprises the following components by mass percentage: 0.1% inorganic transmittance enhancer, 0.3% photocatalyst, 0.6% inorganic film-forming agent and the balance solvent;
[0136] The rest is consistent with Example 5.
[0137] Example 8
[0138] This embodiment provides an inorganic coating, which is different from the embodiment 5 in that it comprises the following components by mass percentage: 0.3% inorganic transmittance enhancer, 0.1% photocatalyst, 0.6% inorganic film-forming agent and the balance solvent;
[0139] The rest is consistent with Example 5.
[0140] Example 9
[0141] This embodiment provides a method for preparing an inorganic coating, which is prepared using the inorganic coating formula of embodiment 1, and specifically comprises the following steps:
[0142] S1. Mix 1 part of zinc acetate with 20 parts of tetraethyl silicate, add to 189 parts of solvent containing diethanolamine, and stir at room temperature for 10 hours to achieve hydrolysis and condensation reaction, thereby obtaining a stable ZnO-SiO 2 Sol.
[0143] S2. Mix 3 parts of zinc acetate with 1 part of titanate, add to 36 parts of solvent containing hydrochloric acid (acid is used to adjust pH to 2-4), stir at room temperature for 16 hours to achieve hydrolysis, then adjust pH to 8 with diethanolamine and continue stirring for 1.5 hours until condensation is completed to obtain stable ZnO-TiO 2 Sol.
[0144] S3. Mix the stable sol obtained by S1 and S2 in proportion, and mix with 10% silica sol, and then dilute with solvent. The mixing ratio of inorganic transmittance enhancer: photocatalyst: inorganic film-forming agent: solvent is 1:20:1:100, and continue stirring for 30 minutes until the solution becomes transparent, to obtain an inorganic transmittance enhancer super hydrophilic self-cleaning dustproof coating that can be stably stored, and the concentration is 0.1% inorganic transmittance enhancer, 2% photocatalyst, 0.1% inorganic film-forming agent, and the rest is solvent.
[0145] Example 10
[0146] This embodiment provides a method for preparing an inorganic coating, which is prepared using the inorganic coating formula of Embodiment 2. The difference from Embodiment 9 is:
[0147] S1. Mix 3 parts of zinc acetate and 1 part of tetraethyl silicate, and add them to 36 parts of solvent containing diethanolamine.
[0148] S2. Mix 1 part of zinc acetate with 10 parts of titanate, and add to 99 parts of solvent containing hydrochloric acid.
[0149] S3 mixes the stable sol obtained by S1 and S2 with the silica sol, and then dilutes the solvent. The mixing ratio of inorganic transmittance enhancer: photocatalyst: inorganic film-forming agent: solvent is 20:1:50:100. The inorganic transmittance enhancer super hydrophilic self-cleaning dustproof coating finally obtained has a concentration of 2% inorganic transmittance enhancer, 0.1% photocatalyst, and 5% inorganic film-forming agent.
[0150] Embodiment 11
[0151] This embodiment provides a method for preparing an inorganic coating, which is prepared using the inorganic coating formula of Embodiment 3, and the difference from Embodiment 9 is:
[0152] S1. Mix 1 part of zinc acetate and 1 part of tetraethyl silicate, and add to 58 parts of solvent containing diethanolamine.
[0153] S2. Mix 1 part of zinc acetate with 5 parts of titanate, and add to 54 parts of solvent containing hydrochloric acid.
[0154] S3 mixes the stable sol obtained by S1 and S2 with the silica sol, and then dilutes the solvent. The mixing ratio of inorganic transmittance enhancer: photocatalyst: inorganic film-forming agent: solvent is 1:10:1:100. The inorganic transmittance enhancer super hydrophilic self-cleaning dustproof coating finally obtained has a concentration of 0.1% inorganic transmittance enhancer, 1% photocatalyst, 0.1% inorganic film-forming agent, and the rest is solvent.
[0155] Example 12
[0156] This embodiment provides a method for preparing an inorganic coating, which is prepared using the inorganic coating formula of embodiment 4, and the difference from embodiment 9 is:
[0157] S1. Mix 2 parts of zinc acetate and 4 parts of tetraethyl silicate, and add them to 54 parts of solvent containing diethanolamine.
[0158] S2. Mix 1 part of zinc acetate with 1 part of titanate, and add to 58 parts of solvent containing hydrochloric acid.
[0159] S3 mixes the stable sol obtained by S1 and S2 with the silica sol, and then dilutes the solvent. The mixing ratio of inorganic transmittance enhancer: photocatalyst: inorganic film-forming agent: solvent is 10:1:20:100. The inorganic transmittance enhancer super hydrophilic self-cleaning dustproof coating finally obtained has a concentration of 1% inorganic transmittance enhancer, 0.1% photocatalyst, 2% inorganic film-forming agent, and the rest is solvent.
[0160] Embodiment 13
[0161] This embodiment provides a method for preparing an inorganic coating, which is prepared using the inorganic coating formula of Embodiment 5, and the difference from Embodiment 9 is:
[0162] S1. Mix 1 part of zinc acetate with 5 parts of tetraethyl silicate and add to 54 parts of solvent containing diethanolamine.
[0163] S2. Mix 2 parts of zinc acetate and 4 parts of titanate, and add them to 54 parts of a solvent containing hydrochloric acid.
[0164] S3 mixes the stable sol obtained by S1 and S2 with the silica sol, and then dilutes the solvent. The mixing ratio of inorganic transmittance enhancer: photocatalyst: inorganic film-forming agent: solvent is 2:2:6:100. The inorganic transmittance enhancer super hydrophilic self-cleaning dustproof coating finally obtained has a concentration of 0.2% inorganic transmittance enhancer, 0.2% photocatalyst, 0.6% inorganic film-forming agent, and the rest is solvent.
[0165] Embodiment 14
[0166] This embodiment provides a method for preparing an inorganic coating, which is prepared using the inorganic coating formula of Example 6, which is consistent with the preparation method of Example 13.
[0167] Embodiment 15
[0168] This embodiment provides a method for preparing an inorganic coating, which is prepared using the inorganic coating formula of Example 7. The difference from Example 13 is that in S3, the mixing ratio of inorganic transmittance enhancer: photocatalyst: inorganic film-forming agent: solvent is 1:3:6:100, and the inorganic transmittance-enhancing super-hydrophilic self-cleaning dust-proof coating finally obtained has a concentration of 0.1% inorganic transmittance enhancer, 0.3% photocatalyst, 0.6% inorganic film-forming agent, and the rest is solvent;
[0169] The rest is consistent with Example 13.
[0170] Example 16
[0171] This embodiment provides a method for preparing an inorganic coating, which is prepared using the inorganic coating formula of Example 8. The difference from Example 13 is that in S3, the mixing ratio of inorganic transmittance enhancer: photocatalyst: inorganic film-forming agent: solvent is 3:1:6:100, and the inorganic transmittance-enhancing super-hydrophilic self-cleaning dust-proof coating finally obtained has a concentration of 0.3% inorganic transmittance enhancer, 0.1% photocatalyst, 0.6% inorganic film-forming agent, and the rest is solvent;
[0172] The rest is consistent with Example 13.
[0173] It should be noted that in Examples 9-16, the solvent is a mixed solution of ethanol and water, and its concentration is 98%; in Examples 9-16, the alcohol amine in step S1 is used to adjust the pH value to 8.5.
[0174] Embodiment 17
[0175] This embodiment provides a method for preparing an inorganic coating, which is prepared using the inorganic coating formula of Embodiment 5, and the difference from Embodiment 13 is:
[0176] S1. Mix zinc acetate and silicate, add to a solvent containing triethanolamine (triethanolamine is used to adjust the pH to 8), and stir at room temperature for 8 hours to achieve hydrolysis and condensation reaction;
[0177] S2 zinc acetate and titanate are mixed, added to a solvent containing sulfuric acid, stirred at room temperature for 7 hours to achieve hydrolysis, and then ethanolamine is used to adjust the pH to 7 and stirred for 2 hours to complete the condensation;
[0178] The solvent in Example 17 is a mixed solution of ethanol and water, and its concentration is 20%;
[0179] The rest is consistent with Example 13.
[0180] Embodiment 18
[0181] This embodiment provides a method for preparing an inorganic coating, which is prepared using the inorganic coating formula of Embodiment 5, and the difference from Embodiment 13 is:
[0182] S1. Mix zinc acetate and silicate, add to a solvent containing ethanolamine (ethanolamine is used to adjust the pH to 9), and stir at room temperature for 12 hours to achieve hydrolysis and condensation reaction;
[0183] S2 zinc acetate and titanate are mixed, added to a solvent containing sulfuric acid, stirred at room temperature for 9 hours to achieve hydrolysis, and then ethanolamine is used to adjust the pH to 9 and stirred for another hour to complete the condensation;
[0184] The solvent in Example 18 is a mixed solution of isopropanol and water, and its concentration is 98%;
[0185] The rest is consistent with Example 13.
[0186] Comparative Example 1
[0187] This comparative example provides an inorganic coating, which is different from Example 5 in that it does not contain an inorganic transmittance enhancer.
[0188] Comparative Example 2
[0189] This comparative example provides an inorganic coating, which is different from Example 5 in that it does not contain a photocatalyst.
[0190] Comparative Example 3
[0191] This comparative example provides a method for preparing an inorganic coating, which is prepared using the inorganic coating formula of comparative example 1. The difference from example 13 is:
[0192] Step S1 is not performed;
[0193] S3. Mix S2 and silica sol in a ratio of 1:3, continue stirring the mixed solution, dilute the solvent 100 times, that is, the mixing ratio of photocatalyst: inorganic film-forming agent: solvent is 1:3:100, continue stirring for 30 minutes until the solution is completely uniform and transparent, and obtain a coating with a concentration of 0.2% photocatalyst, 0.6% inorganic film-forming agent, and the rest solvent.
[0194] Comparative Example 4
[0195] This comparative example provides a method for preparing an inorganic coating, which is prepared using the inorganic coating formula of comparative example 2, and the difference from example 13 is:
[0196] Step S2 is not performed;
[0197] S3. S1 and silica sol are mixed in a ratio of 1:3, and the mixed solution is continuously stirred. The solvent is diluted 100 times, that is, the mixing ratio of inorganic permeability enhancer: inorganic film-forming agent: solvent is 1:3:100. Stirring is continued for 30 minutes until the solution is completely uniform and transparent to obtain a coating having a concentration of 0.2% inorganic permeability enhancer, 0.6% inorganic film-forming agent, and the rest being solvent.
[0198] Test Case
[0199] Test samples: the inorganic coatings prepared in Examples 9-18, the inorganic coatings prepared in Comparative Examples 3-4, and blank glass.
[0200] Test method: Use brush coating to apply on the slope of installed photovoltaic panels, and perform secondary construction after drying. The data results are shown in Table 1.
[0201] The specific test items and test methods are as follows: (1) Transmittance: Tested with an optical transmittance meter. Since photovoltaic glass and architectural glass are most concerned about the transmittance in the visible light range, the transmittance in the visible light range is recorded and compared; the transmittance is tested on transparent glass using a 2mm optical glass sheet. (2) Water contact angle: Tested with a contact angle meter. (3) Surface resistance: Measured with a surface resistance meter. (4) Adhesion: The coating adhesion is tested by cross-cutting test in accordance with GB / T9286-1998.
[0202] Table 1: Performance Test
[0203]
[0204] It can be seen from the data in Table 1 that compared with Example 13, Comparative Examples 3 and 4 do not contain inorganic transmittance enhancers and photocatalysts, respectively, and the product effects of Comparative Examples 3 and 4 are worse than those of Example 13; Compared with Example 13, Example 15 replaces part of the transmittance enhancer with part of the photocatalyst, and the results show that the transmittance enhancer effect decreases, but the photocatalytic effect increases insignificantly, indicating that the photocatalytic amount in Example 13 is sufficient and does not need to be further increased; Compared with Example 13, Example 16 replaces part of the photocatalyst with part of the transmittance enhancer, and the results show that the photocatalytic effect decreases, and the transmittance increase is not obvious, indicating that the amount of transmittance enhancer in Example 13 is reasonable; It can be seen that the formula ratio of the inorganic coating in Example 13 is the optimal ratio, and it has the best effect in transmittance enhancement, photocatalytic super hydrophilic self-cleaning, and anti-static and dustproof.
[0205] in, Figure 1 This is a diagram showing the dust-proof effect of the inorganic coating prepared in Example 13 after being applied to the inclined surface of a photovoltaic panel; Figure 2 This is a dustproof effect diagram of an existing photovoltaic panel without any treatment. It can be seen that the coating formed by the inorganic coating provided by the embodiment of the present invention has a better dustproof effect.
[0206] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An inorganic coating, characterized in that: The inorganic coating comprises the following components by mass percentage: 0.2% inorganic transmittance enhancer, 0.2% photocatalyst, 0.6% inorganic film-forming agent and the balance solvent; Wherein, the inorganic transmittance enhancer comprises ZnO-SiO2 sol, and the photocatalyst comprises ZnO-TiO2 sol; The inorganic permeability enhancer is prepared by hydrolyzing zinc salt and silicate, wherein the molar ratio of zinc salt to silicate is 1:5; the silicate includes tetraethyl silicate; The zinc salt and the silicate are mixed and reacted to obtain an inorganic permeability enhancer; the process of mixing the zinc salt and the silicate further comprises: adding a solvent containing an alcohol amine, stirring at room temperature, and reacting; The photocatalyst is prepared by hydrolyzing zinc salt and titanate, and the molar ratio of zinc salt to titanate is 2:4; The zinc salt and the titanate are mixed to react to obtain a photocatalyst; the process of mixing the zinc salt and the titanate further comprises: adding the mixture to a solvent containing an acid, stirring at room temperature, performing a primary reaction, and then adjusting the pH to 7-9, stirring at room temperature, and performing a secondary reaction; The inorganic film-forming agent includes silica sol; The preparation method of the inorganic coating comprises the following steps: The inorganic transmittance enhancer, the photocatalyst and the inorganic film-forming agent are mixed to obtain the inorganic coating.
2. The inorganic coating according to claim 1, characterized in that: The zinc salt used to prepare the inorganic permeability enhancer includes at least one of zinc acetate and zinc chloride.
3. The inorganic coating according to claim 1, characterized in that: The zinc salt used to prepare the photocatalyst includes at least one of zinc acetate and zinc chloride; The titanate includes at least one of ethyl titanate, isopropyl titanate, and butyl titanate.
4. The inorganic coating according to claim 1, characterized in that: The silica sol includes at least one of acidic silica sol, alkaline silica sol and neutral silica sol; The particle size of the silica sol is 2 nm-200 μm.
5. The method for preparing an inorganic coating according to any one of claims 1 to 4, characterized in that: The following steps are involved: The inorganic transmittance enhancer, the photocatalyst and the inorganic film-forming agent are mixed to obtain the inorganic coating.
6. The preparation method according to claim 5, characterized in that: The zinc salt and the silicate are mixed and reacted to obtain an inorganic permeability enhancer; The process of mixing the zinc salt and the silicate also includes: adding a solvent containing an alcohol amine, stirring at room temperature, and reacting; The alcoholamine includes at least one of ethanolamine, diethanolamine and triethanolamine; The stirring time is 8-12 h.
7. The preparation method according to claim 5, characterized in that: The zinc salt and the titanate are mixed and reacted to obtain a photocatalyst; The process of mixing the zinc salt and the titanate also includes: adding to a solvent containing an acid, stirring at room temperature, and performing a primary reaction, and then adding to adjust the pH to 7-9, stirring at room temperature, and performing a secondary reaction; The acid agent includes at least one of hydrochloric acid, acetic acid, phosphoric acid and sulfuric acid; The pH is adjusted by adding alcohol amine; The stirring time of the primary reaction is 7-9 h; The stirring time of the secondary reaction is 1-2 h.
8. Use of the inorganic coating according to any one of claims 1 to 4 or the inorganic coating prepared by the method for preparing the inorganic coating according to any one of claims 5 to 7 in surface treatment of inorganic materials.
Citation Information
Patent Citations
Ultra-hydrophilic self-cleaning anti-fog coat and its preparation method and use
CN101168475A
Method for improving chemical stability of zinc oxide transparent electric conduction film
CN107217232A
Composite self-cleaning nanometer coating, inorganic transparent coating layer and self-cleaning product
CN107892826A
Composite broadband antireflecting film and preparation method thereof
CN102190448A
Super-hydrophilic self-cleaning coating material composition and preparation method thereof, and super-hydrophilic self-cleaning glass and preparation method thereof
CN110093050A